Could social support mediate the relationship between personality trait patterns and mental health in Chinese older adults: a nationwide cross-sectional study conducted in 2022 - Yanming Liao; Shujuan Xiao; Xiao Zheng; Xinru Li; Benli Xue; Lingli Yang; Mengjie Zhang; Qiyu Li; Yibo Wu; Chichen Zhang (BMC Public Health)
Abstract Objectives This study aims to examine the personality trait patterns of older adults, investigate the influence of personality traits on their mental health, and explore the mediating role of social support in the relationship among personality trait patterns, personality traits and mental health. Methods This study utilized a cross-sectional design, with 4,197 participants from the psychology and behavior investigation of Chinese residents in 2022 (PBICR2022). Latent profile analysis (LPA) was conducted to identify distinct personality profiles, and multiple linear regression and mediation analyses were performed to examine the relationships among personality trait patterns, personality traits, social support, and mental health. Results The LPA identified four distinct personality profiles among older adults. Multiple linear regression revealed that Extraversion, Agreeableness, Conscientiousness, and Openness were positively associated with better mental health, whereas Neuroticism was negatively associated with mental health. Social support was found to partially mediate the effects of Extraversion, Agreeableness, Conscientiousness, Neuroticism, Agreeable-Conscientious Personality and Extraverted-Low Neuroticism Personality on mental health and to fully mediate the effect of Openness and Extraverted-Conscientious Personality. Limitations The study’s cross-sectional design limits the ability to draw causal inferences about the relationships among personality traits, social support, and mental health. Additionally, the reliance on self-reported measures may introduce bias. Conclusions This study demonstrated that personality traits and social support are crucial determinants of mental health in older adults. Social support plays a significant mediating role, suggesting that interventions aimed at enhancing social networks could be particularly effective in improving mental health for older adults.